Foraminifer, diatom frustules, and total organic carbon of sediment cores EMB046_6-5GC, EMB046_10-4GC, and EMB046_20-3GC in the Norwegian Trench and the Skagerrak - Irina Polovodova Asteman; Bjørg Risebrobakken; Matthias Moros; Anna Binczewska; Slawomir Dobosz; Eystein Jansen; Joanna Slawinska; Malgorzata Bak (PANGAEA, 2017)
To detect climatic linkages between the Baltic Sea, the Skagerrak and the Nordic Seas, we present multi-proxy reconstructions covering the last 4500 years from three sediment cores taken in the Skagerrak and along the SW Norwegian margin. Foraminiferal assemblages at all three sites show a distinct change at c. 1700 years BP, associated with a transition from absence and rare occurrence of Brizalina skagerrakensis during c. 4500–2300 years BP to its subsequent abundance increase, suggesting a stronger influence of nutrient-rich water-masses during the last c. 1700 years. Increased nutrient availability, which probably stimulated higher primary productivity, is further supported by an increase in diatoms, total organic carbon and benthic foraminiferal species indicative of high productivity and carbon fluxes during the last c. 1700 years as compared to c. 4500–2300 years BP. The amplitude of the B. skagerrakensis signal is largest in the central Skagerrak and gradually becomes smaller towards the Norwegian Sea suggesting that the dominant source of the nutrient-rich water was the brackish outflow from the Baltic Sea. The generally lower abundances of planktonic foraminifera since c. 1700 years BP support the hypothesis of less saline surface water conditions in the Skagerrak. These results agree with other studies, which suggest a stronger Baltic outflow over the last 1700 years coinciding with a general cooling, increased wintertime westerlies bringing more winter precipitation to northern Europe, increased river runoff and higher frequency of floods. The increase in outflow also occurs during deposition of laminated sediments in the deep Baltic Sea. Leakage of dissolved inorganic phosphorus from anoxic sediments, as well as enhanced erosion due to deforestation in combination with higher runoff from Norway, coastal upwelling and more vigorous frontal dynamics may all have contributed to higher nutrient availability within the adjacent Skagerrak during the last 1700 years BP as compared to c. 4500–2300 years BP, when low productivity prevailed in the study area.
Supplement to: Polovodova Asteman, I et al. (2018): Late Holocene palaeoproductivity changes: a multi-proxy study in the Norwegian Trench and the Skagerrak, North Sea. Boreas, 47(1), 238-255, https://doi.org/10.1111/bor.12264